Value in Colorectal Cancer Treatment: Where It Is Lacking, and Why. Issue 3 (May 2016) - Saltz, Leonard B.
Abstract : Abstract: Treatment options have improved for patients with colorectal cancer, but these improvements have invariably been more modest than had been anticipated or hoped for. Yet while outcomes have improved modestly, costs have risen substantially, as prices of the newer anticancer agents in colorectal cancer have led the way in the stratospheric rise in cancer drug prices in general. Development of future strategies that will be both sustainable and attainable by all who need them will require both an understanding of past events that have brought us to the present and a willingness to confront the limitations of our present options and to assess them for the true value that they do or do not offer.